2022
DOI: 10.1038/s41598-022-23904-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of beverage temperature on consumer preferences for black coffee

Abstract: We recently performed a systematic investigation of consumer preferences for black coffee versus key brewing parameters, including total dissolved solids, extraction yield, and brewing temperature (Cotter et al. in J Food Sci 86(1):194–205, 2021. https://doi.org/10.1111/1750-3841.15561). An experimental goal in that work was for participants to taste the coffee at a beverage temperature of 65 °C, but the large sample size of more than 3000 individual tastings, combined with natural variations in the brewing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The authors observed that women were more sensitive to changes in the drink's temperature in terms of sensory and emotional responses. Ristenpart et al (2022) also noted that preference changes with changes in coffee temperature, having a crucial temperature range in which coffee becomes unacceptable for consumers.…”
Section: Resultsmentioning
confidence: 99%
“…The authors observed that women were more sensitive to changes in the drink's temperature in terms of sensory and emotional responses. Ristenpart et al (2022) also noted that preference changes with changes in coffee temperature, having a crucial temperature range in which coffee becomes unacceptable for consumers.…”
Section: Resultsmentioning
confidence: 99%
“…(11) The total hardness of water directly affects the taste of water and the palatability of brewed coffee (12) as coffee is prepared in few minutes using hot water close to the boiling point. (13) In addition to the total hardness, the temperature of the brewing water is also important to the taste of brewed coffee. (14) With the increasing demand for coffee with unique taste and flavor, cold-brew coffee, which is prepared using water at a temperature of 20−25°C or lower, has gained much popularity recently, but a longer brewing time from 8 to 24 h is required.…”
Section: Introductionmentioning
confidence: 99%
“…(14) With the increasing demand for coffee with unique taste and flavor, cold-brew coffee, which is prepared using water at a temperature of 20−25°C or lower, has gained much popularity recently, but a longer brewing time from 8 to 24 h is required. (13,15) To brew coffee with a satisfying taste and flavor, it is important to maintain constant water quality and temperature. Therefore, we developed a coffee pot monitoring system with a longrange radio (LoRa) module in which sensors are used to control the temperature, quality, and amount of water.…”
Section: Introductionmentioning
confidence: 99%